Top of 250-pound autoclave (1937)
General view of the top of a 250-pound autoclave used during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. During production, a partially-evaporated nylon salt solution was fed into the autoclave and heated to 275 degrees centigrade under a pressure of 275 pounds per square inch in order to precipitate polymerization. Once polymerization occurred, additional water was bled off and the pressure was slowly reduced to atmospheric levels before the polymer was extruded. Notably, two chemicals were added to the autoclave during the process: acetic acid to stop polymerization once the molecules reached the desired length and titanium dioxide to keep the nylon from becoming glassy and allow the finished product to more closely resemble silk.
Keywords: Nylon; Nylon--Testing; E.I. du Pont de Nemours & Company; Machinery; Autoclaves